2017
DOI: 10.1038/cddis.2017.511
|View full text |Cite
|
Sign up to set email alerts
|

Increased 15-lipoxygenase-1 expression in chondrocytes contributes to the pathogenesis of osteoarthritis

Abstract: 15-Lipoxygenase-1 (15-LO-1) is involved in many pathological processes. The purpose of this study was to determine the potential role of 15-LO-1 in osteoarthritis (OA). The levels of 15-LO-1 expression were measured by western blotting and quantitative real-time PCR in articular cartilage from the OA rat models and OA patients. To further investigate the effects of 15-LO-1 on chondrocyte functions, such as extracellular matrix (ECM) secretion, the release of matrix-degrading enzymes, the production of reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In the present study, we confirmed that OA-related factors, including IL-1β, TNF-α and mechanical stress significantly increased the expression of PAK1 in chondrocytes. All these OA-related factors, IL-1β was recognized as the most important inflammatory cytokines in the pathogenesis of OA [15]. IL-1β was confirmed to induce inflammatory reactions and catabolic effect independently as well as being combined with other mediators with respect to the articular cartilage and other elements of joints [27].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the present study, we confirmed that OA-related factors, including IL-1β, TNF-α and mechanical stress significantly increased the expression of PAK1 in chondrocytes. All these OA-related factors, IL-1β was recognized as the most important inflammatory cytokines in the pathogenesis of OA [15]. IL-1β was confirmed to induce inflammatory reactions and catabolic effect independently as well as being combined with other mediators with respect to the articular cartilage and other elements of joints [27].…”
Section: Discussionmentioning
confidence: 93%
“…Under isoflurane anesthesia (3-5% sleep box induction maintained at 2% via mask inhalation), fur was removed and skin was prepared using povidone-iodine and alcohol in triplicate. Joint capsule was incised and the medial meniscotibial ligament was sectioned, as described previously [15]. In the sham operation group, the joint cavities were opened without any treatment.…”
Section: Cartilage Samples From Oa Models Rats and Patients With Oamentioning
confidence: 99%
“…Interestingly, despite the significant expression of 15-LOX in the synovium, patients suffering from RA did not correlate with the concentration of 15-HETE in synovial fluid. In addition to enhancing immune cell chemotaxis to the focus of inflammation through NF-κB induction, the proinflammatory action of 15-LOX in RA relies on increasing vascular permeability, increasing TNF-α expression in vascular smooth muscle, as well as inhibiting proliferation and induction of chondrocyte apoptosis [63]. Despite the proven proinflammatory effect, it should be emphasized that the reaction products catalyzed by 15-LOX may paradoxically exhibit anti-inflammatory properties in RA as, for example, in the case of lipoxins.…”
Section: Duration Of Symptoms § § Scorementioning
confidence: 99%
“…Osteoarthritis (OA), also known as degenerative arthritis or senile arthritis, is a degenerative disease. 1 Increased obesity, age, trauma to joint areas, excessive manual labour and decreased muscle strength and joint stability are important risk factors for OA. 2–5 The main clinical manifestations of OA are chronic pain, joint instability, stiffness, joint deformity and reduced imaging of the joint space; these manifestations eventually lead to progressive disability and reduce patient quality of life.…”
Section: Introductionmentioning
confidence: 99%
“… 2–5 The main clinical manifestations of OA are chronic pain, joint instability, stiffness, joint deformity and reduced imaging of the joint space; these manifestations eventually lead to progressive disability and reduce patient quality of life. 1 6 Worldwide, OA, particularly OA of the knee and hip joints, is one of the leading causes of disability among the older adults. 7 8 Research has shown that around one-third of older adults have OA.…”
Section: Introductionmentioning
confidence: 99%